Resilience and health among youths with documented childhood maltreatment - Maia, Ângela (2012)
Background: The aim of this study was to assess the current health among youths who were maltreated as a child and had received one of two different protective interventions (home vs. institutionalization). Methods: We assessed the childhood adversity, psychopathology, physical complaints and health risk behaviours of 136 youths who had been identified by Child Protective Services and 80 youth not identified (control). Findings: The groups were similar in terms of psychopathology, global index of risk behaviours, and physical complaints. However, some of the risk behaviours were associated with different groups. Discussion: The literature has shown that maltreated children have a heightened risk of developing health problems, but our results suggest resilience and the importance of CPS intervention after maltreatment identification. However, CPS professionals, schools and communities need to focus on the strategies for health promotion and prevention of risk behaviours considering different young populations.